Adenovirus, Chlamydia psittaci e Circovirus em Amazona aestiva: ocorrência, lesões e aspectos do tráfico e de manejo no CETAS de Belo Horizonte - Érika Procópio Tostes Teixeira (2020)
The blue-fronted amazon parrot (Amazona aestiva) is the most captured psittacine in the world, being one of the biggest focus in the illegal trade of wild animals. Trafficked birds are transported and kept in stressful conditions leading to immunodepression and primary or opportunistic infections. The objective of this study was investigate the occurrence of adenovirus, circovirus of beak and feather disease (BFDV) and Chlamydia psittaci in trafficked blue-fronted amazon parrot nestlings recently received at the Wild Animal Triage Center in Belo Horizonte (CETAS/BH). Psittacines (n=114) that died within 6 months of triage were necropsied, and livers were collected for molecular analysis. Results showed the 81/114 (71%) parrots were positive for adenovirus, indicating that they could have been apprehended already infected and that the virus circulated in CETAS during captivity. No positivity was detected for circovirus or Chlamydia, indicating that the animals entered and remained free during the triage process. Introduced management changes in the handling of rescued psittacines in CETAS/BH, including the prophylactic antibiotic therapy with doxycycline, were considered associated beneficial on the prevention of the previously reported present C. psittaci transmission